Origin of osteoclasts: mature monocytes and macrophages are capable of differentiating into osteoclasts under a suitable microenvironment prepared by bone marrow-derived stromal cells. - Udagawa, N (1990)
We previously reported that osteoclast-like cells were formed in cocultures of a mouse marrow-derived stromal cell line (ST2) with mouse spleen cells in the presence of 1 alpha, 25-dihydroxyvitamin D3 and dexamethasone. In this study, we developed a new coculture system to determine the origin of osteoclasts. When relatively small numbers of mononuclear cells (10(3)-10(5) cells per well) obtained from mouse bone marrow, spleen, thymus, or peripheral blood were cultured for 12 days on the ST2 cell layers, they formed colonies with a linear relationship between the number of colonies formed and the number of hemopoietic cells inoculated. Tartrate-resistant acid phosphatase (TRAPase)-positive mononuclear and multinucleated cells appeared in the colonies (TRAPase-positive colonies) in response to 1 alpha, 25-dihydroxyvitamin D3 and dexamethasone. When hemopoietic cells suspended in a collagen-gel solution were cultured on the ST2 cell layers to prevent their movement, TRAPase-positive colonies were similarly formed, indicating that each colony originated from a single cell. All of the colonies consisted of nonspecific esterase-positive cells. The monocyte-depleted population prepared from peripheral blood failed to form colonies, whereas the monocyte-enriched population produced a large number of TRAPase-positive colonies. In addition, alveolar macrophages formed TRAPase-positive colonies most efficiently on the ST2 cell layers in the presence of the two hormones. Salmon 125I-labeled calcitonin specifically bound to the TRAPase-positive cells. Resorption lacunae were formed on dentine slices on which cocultures were performed. When direct contact between the peripheral blood cells and the ST2 cells was inhibited by a collagen-gel sheet, no TRAPase-positive cells were formed. These results indicate that osteoclasts are also derived from the mature monocytes and macrophages when a suitable microenvironment is provided by bone marrow-derived stromal cells.